A Study on the Factors Influencing College Students' Alternative Search Behavior for Online Health Information (The Journal of Medicine, Humanity and Media, 2024)
Alternative health information seeking is an important way for older adults to access health support. In this study, we took college students who had conducted online health information substitution search for the elderly at home as the research subjects, and used the extended Comprehensive Model of Information Seeking (CMIS) as the theoretical framework to explore the behavioral characteristics and influencing factors of college students' online health information substitution search for the elderly at home through the questionnaire method (N=321), with a view to providing new ideas for the dissemination of health information to the elderly population. The study found that the content and search platforms of college students' alternative health information searching for the elderly at home are relatively basic; the influence of health awareness pressure on alternative health information searching behavior is not significant, and there may be other potential emotional mediators as well as insufficient behavioral internal motivation; filial piety culture influences the college students' alternative health information searching behavior through the utility of the information carrier; self-efficacy is an intrinsic motivation for intergenerational feedback; and the influence of self-efficacy is a key factor in college students' alternative health information searching behavior. Self-efficacy, as an intrinsic motivation for intergenerational feedback, is also an important factor influencing online health information alternative search behavior.
Keywords: Online health information; Alternative search behaviors; Comprehensive model of information seeking; Older adults